PERSEPSI MASYARAKAT PETANI TERHADAP DAMPAK LAHAN KRITIS - Sulistya Rini Pratiwi; Yohanna Thresia Nainggolan (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2022)
This study aims to determine farmers' perceptions of the impact of degraded land in Tarakan City. The research was conducted at the agricultural center of Juata Permai Village. This research is a descriptive study using a qualitative approach. The data collection methods used were a questionnaire and in-depth interviews. The results of the score calculation related to farmers' understanding of the impact of degraded land are not good. This shows that the level of knowledge and understanding among farmers about the impacts of degraded land is still low. In terms of government response, an average of 31.37 was obtained, and it was included in the unfavorable category. This shows that the government's prevention policies are relatively ineffective and tend to be less informative. Overall, this shows that farmers' appreciation of critical land improvement is included in the agree category.